Perbandingan Efektivitas Pembelajaran Menggunakan ChatGPT dan Buku Teks Terhadap Hasil Belajar dan Prestasi Siswa SMP Negeri 7 Kuningan - Ibrahim, Maolana; Mahpudin, Asep (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the differences in the effectiveness of learning using ChatGPT and textbooks on learning outcomes and student achievement at SMP Negeri 7 Kuningan. This study uses a quantitative approach with a quasi-experimental design (post-test only control group design). The study population was all seventh-grade students of SMP Negeri 7 Kuningan, with class VII A as the control group (textbook learning) and class VII B as the experimental group (learning using ChatGPT), each totaling 40 students. The research instruments included learning outcome tests (pretest and posttest), student response questionnaires, and observations. Data analysis was carried out using the Shapiro-Wilk normality test, Levene's homogeneity test, and the mean difference test with the independent sample t-test. The results showed a significant difference (p < 0.05) between the experimental and control groups. The average posttest score for the experimental group was 82.75, while the control group's score was only 74.25. Furthermore, more than 85% of students responded positively to the use of ChatGPT, especially in terms of interest, engagement, and learning independence. Observations also showed that students who used ChatGPT were more active in asking questions and discussing. Thus, ChatGPT proved more effective than textbooks in improving student learning outcomes and achievement.